Formation of hub–filament structure triggered by a cloud–cloud collision in the W33 complex. Issue 2 (6th December 2022) - Zhou, Jian-Wen; Li, Shanghuo; Liu, Hong-Li; Peng, Yaping; Zhang, Siju; Xu, Feng-Wei; Zhang, Chao; Liu, Tie; Li, Jin-Zeng
ABSTRACT: Hub–filament systems are suggested to be the birth cradles of high-mass stars and clusters, but the formation of hub–filament structure is still unclear. Using FUGIN 13 CO (1–0), C 18 O (1–0) and SEDIGISM 13 CO (2–1) survey data, we investigate the formation of hub–filament structure in the W33 complex. The W33 complex consists of two colliding clouds, called W33-blue and W33-red. We decompose the velocity structures in W33-blue by fitting multiple velocity components and find a continuous and monotonic velocity field. Virial parameters of Dendrogram structures suggest the dominance of gravity in W33-blue. The strong positive correlation between velocity dispersion and column density indicates that the non-thermal motions in W33-blue may originate from gravitationally driven collapse. These signatures suggest that the filamentary structures in W33-blue result from the gravitational collapse of a compressed layer. However, the large-scale velocity gradient in W33-blue may originate mainly from cloud–cloud collision and feedback of active star formation, instead of filament-rooted longitudinal inflow. From the results observed above, we argue that cloud–cloud collision triggers the formation of hub–filament structures in the W33 complex. Meanwhile, the appearance of multiple-scale hub–filament structures in W33-blue is likely an imprint of the transition from a compressed layer to a hub–filament system.